2018
DOI: 10.1088/1757-899x/352/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ratio between rigid plant height and water depth on the manning’s coefficient in open channel

Abstract: Abstract. One of the important factors in channel dimension is the Manning's coefficient (n).This coefficient is influenced not only by the channel roughness but also by the presence of plants in the channel. The aim of the study is to see the effect of the ratio between the height of the rigid plant and water depth on the Manning's coefficient (n) in open channel. The study was conducted in open channel with 15.5 m long, 0.5 m wide and 1.0 m high, in which at the center of the channel is planted with the rigi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The procedure of research method which is applied in this research is the same as and follows the previous research done by [6][7][8][9]. The difference is only on placing vegetation treatments and method of data analysis.…”
Section: Experimental Designs and Methodsmentioning
confidence: 99%
“…The procedure of research method which is applied in this research is the same as and follows the previous research done by [6][7][8][9]. The difference is only on placing vegetation treatments and method of data analysis.…”
Section: Experimental Designs and Methodsmentioning
confidence: 99%
“…Fig. 24 Relationship between the calculated relative specific energy (E rc ) and predicted relative specific energy (E rp ) for the un-grassed canal…”
Section: Gep Spssmentioning
confidence: 99%
“…However, the GEP model, which produced a physical equation that is applicable in engineering practice, would be preferred. Rizalihadi et al [24] studied the effect of the ratio between the height of the rigid plant and water depth on Manning's coefficient (n) in an open channel. The results showed that the mean velocity becomes decreases 17.81-34.01% as increase the ratio of Hplants/Hwater.…”
Section: Introductionmentioning
confidence: 99%